LÍNGUA E RESISTÊNCIA: QUESTÕES E CASOS REPRESENTATIVOS DESTA RELAÇÃO - da Costa Souza, Paula (Revista (Entre Parênteses), 2023)
In this essay, some considerations, reflections and examples are presented that are n unfolding of a speech in an academic event. Theoretical contributions come from the Sociolinguistic framework, such as Lagares (2011), Calvet (2002) and Monteagudo (2012). By relating the theoretical discussions with different examples, it is intended to question the relationship between language and power.